2017
DOI: 10.1096/fj.201700275r
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting mitochondrial and oxidative vulnerabilities with a synthetic analog of pancratistatin in combination with piperlongumine for cancer therapy

Abstract: Harsh adverse effects as a result of nonspecific targeting of chemotherapeutics currently pose obstacles in cancer therapy; thus, it would be invaluable to devise novel approaches to specifically target cancer cells. The natural compound pancratistatin (PST) has been shown to preferentially induce apoptosis in a variety of cancer cell types. Recently, several analogs of PST were shown to be efficacious in inducing apoptosis in a variety of aggressive cancer cell types cancer cell mitochondrial targeting; it ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 34 publications
(49 reference statements)
0
8
0
Order By: Relevance
“…Additionally, literature reports also indicated the possibility of combining PL with other substances of natural origins. The available data indicate that treatments with pancratystatin (PST) and PL cause areduction in the survival of pancreatic cancer cells [55]. Similar combinations with cytostatics have been studied in the case of the second alkaloid used-SAN.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, literature reports also indicated the possibility of combining PL with other substances of natural origins. The available data indicate that treatments with pancratystatin (PST) and PL cause areduction in the survival of pancreatic cancer cells [55]. Similar combinations with cytostatics have been studied in the case of the second alkaloid used-SAN.…”
Section: Discussionmentioning
confidence: 99%
“…Tamoxifen is a well-tolerated ER antagonist used for ER positive breast cancer patients and has also been shown to target the mitochondria and induce autophagy [36]. A synergistic induction of apoptosis and autophagy was observed when tamoxifen was combined with an analog of pancratistatin, another mitochondria targeting compound [14]. Likewise, when tamoxifen was combined with curcumin, a synergistic induction of apoptosis and autophagy was observed [29].…”
Section: Discussionmentioning
confidence: 99%
“…Induction of cancer cell death selectively can occur through targeting the unique characteristics of cancerous cells. For example, analogs of the natural compound pancratistatin (PST) were able to induce apoptosis selectively in cancer cells through disrupting the mitochondrial membrane potential and the release of apoptogenic factors [14,15]. Cancer cells also display higher basal levels of reactive oxygen species (ROS), which promotes tumor proliferation and progression [16,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our studies on PST analog SVTH-7 indicated that combination treatment with oxidative stress inducing piperlongumine (PL) led to a more efficacious treatment that dissipated the MMP, decreased oxygen consumption, and induced the release of many apoptogenic factors from the mitochondria [155]. Because of the hyperpolarization of the mitochondria in cancer cells, the PST analogs were able to selectively target cancer, possibly through the processing and uptake of PST analogs in positively charged molecules to be brought to only cancer cell mitochondria.…”
Section: Strategies To Target Mitochondriamentioning
confidence: 99%